Assessing the Quality of Third Places in Nakhon Ratchasima Old Town Through the Analytical Hierarchy Process (Ahp) - Seemuangngam, Apinan; Padkoh, Nittaya; Gapphimai, Srivieng; Wuttipongpreecha, Kanjana; Chaijan, Supachai (International Journal of Building, Urban, Interior and Landscape Technology, 2025)
Third Places foster informal social interaction beyond home and work. Spatial and design features greatly influence how these places function and are perceived. Many characteristics of these places are linked to public spaces; however, simply having numerous public areas does not guarantee that third places meet residents’ needs. Nakhon Ratchasima Old Town demonstrates this issue. Many public areas look attractive but are socially disconnected and underused. This study employs the Analytical Hierarchy Process (AHP) to assess the Old Town’s Third Places based on eight key factors. Results show that safety, efficiency, and accessibility are the top priorities. Still, the rankings differ among professionals, suggesting that practical improvements should address the diverse needs and traits of residents, rather than focusing solely on aesthetic upgrades. By integrating expert judgment with a systematic evaluation, the research provides evidence-based guidance for identifying, ranking, and implementing initiatives that improve social functionality, increase community engagement, and preserve the livability of the historic town center. The findings emphasize that successful revitalization depends on social value driving design decisions, ensuring public spaces serve as proper third places rather than mere visual features.